2021
DOI: 10.7717/peerj.10699
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF levels and the antidepressant effects of electroconvulsive therapy with ketamine anaesthesia: a preliminary study

Abstract: Objective To firstly examine the relationship between serum brain-derived neurotrophic factor (BDNF) levels and antidepressant response to ketamine as an anaesthesia in electroconvulsive therapy (ECT) in Chinese patients with treatment-refractory depression (TRD). Methods Thirty patients with TRD were enrolled and underwent eight ECT sessions with ketamine anaesthesia (0.8 mg/kg) alone. Depression severity, response and remission were evaluated using the 17-item Hamilton Depression Rating Scale (HAMD-17). En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Moreover, several studies have reported that patients who were remitters after receiving ECT had higher baseline levels of BDNF than non-remitters [ 11 ], suggesting that baseline BDNF levels may be more important in predicting remission than the ECT-induced modulation of BDNF [ 12 ]. However, the baseline differences between future remitters and non-remitters have not been observed in other studies [ 13 , 14 ], leaving much room for further investigation.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, several studies have reported that patients who were remitters after receiving ECT had higher baseline levels of BDNF than non-remitters [ 11 ], suggesting that baseline BDNF levels may be more important in predicting remission than the ECT-induced modulation of BDNF [ 12 ]. However, the baseline differences between future remitters and non-remitters have not been observed in other studies [ 13 , 14 ], leaving much room for further investigation.…”
Section: Introductionmentioning
confidence: 89%
“…The mechanism by which it determines an antidepressant effect is complex and not entirely clear [32]. ECT affects neurotransmission [33][34][35], induces changes in neuroendocrine [36] and neurotrophic factors [37][38][39][40], and also alters inflammatory mechanisms [41]. Some studies also showed that ECT can induce structural changes in the brain [42,43].…”
Section: Introductionmentioning
confidence: 99%